The Influence of Reading English Comics on A Student’s English Subject Achievement at School (RETAIN, 2013)
In their age, students tend to spend their spare time to do the things that they are interested in. One of those is reading comics. Comics that students read are not only in Bahasa Indonesia, but also in English. Some of the students love to read English comics. Reading English comics continuously will have influence on the students’ English subject achievement at school. The researcher conducted this research to inform the reader about the influence of reading English comics on the student’s English subject achievement at school. Hopefully, this research will give input to several parties whom concern. This research is limited to one student who likes reading English comics. Case study research was used to answer the research problem. This type of research was used because the problem was seen as particular cases that were needed to be solved. Through this study, the researcher investigated and explained the influence of reading English comics on the student’s English subject achievement at school. This study covered all of English skills, except listening. All those result and discussion can be concluded that English comics have really great effect on the student’s comprehension and ability to infer something in reading. Besides that, English comics also have great effect on the student’s English vocabulary mastery in composing writing. English comics really help student in reading and writing, but speaking.Key words: Reading, Comics, Influence, English ability. Abstrak Di usia mereka, siswa cenderung menghabiskan waktu luang mereka untuk melakukan hal-hal yang menarik bagi mereka. Salah satunya adalah membaca komik. Komik yang dibaca oleh para siswa tidak hanya dalam Bahasa Indonesia, tetapi juga dalam Bahasa Inggris. Beberapa siswa gemar membaca komik berbahasa Inggris. Membaca komik berbahasa Inggris secara terus menerus akan memiliki pengaruh terhadap prestasi belajar Bahasa Inggris siswa di sekolah. Peneliti melakukan penelitian ini untuk menginformasikan pembaca tentang pengaruh membaca komik berbahasa Inggris pada prestasi siswa dalam bidang studi Bahasa Inggris di sekolah. Penelitian ini diharapkan akan memberikan masukan kepada beberapa pihak yang berkepentingan. Penelitian ini terbatas pada satu siswa yang suka membaca komik berbahasa Inggris. Penelitian studi kasus digunakan untuk menjawab masalah dalam penelitian. Jenis penelitian ini digunakan karena masalah yang timbul dipandang sebagai kasus-kasus tertentu yang perlu dipecahkan. Melalui studi ini, peneliti menyelidiki dan menjelaskan pengaruh membaca komik berbahasa Inggris pada prestasi siswa dalam bidang studi Bahasa Inggris di sekolah. Studi ini mencakup semua kemampuan bahasa Inggris, kecuali mendengarkan. Dari hasil dan pembahasan dari permasalahan tersebut, dapat disimpulkan bahwa komik berbahasa Inggris memiliki pengaruh yang sangat besar pada pemahaman dan kemampuan untuk menyimpulkan sesuatu dalam keahlian membaca siswa. Selain itu, komik berbahasa Inggris juga memiliki efek besar pada penguasaan kosakata siswa dalam menyusun tulisan. Komik berbahasa Inggris benar-benar membantu siswa dalam membaca dan menulis, tapi tidak dalam hal berbicara. Kata Kunci: Membaca, Komik, Pengaruh, Kemampuan Berbahasa Inggris.